The impact of cooperative learning and direct instruction on Saravan Islamic Azad university student’s math progress in first half of educational year 2013-2014 - Parsafar, Abdol Hamid; Nosrat, Azizollah (International Journal of Applied Mathematical Research, 2018)
The aim of this study is to compare the impact of cooperative learning and direct instruction on Saravan Islamic Azad University student’s math progress in first half of educational year 2013-2014. Research method is semi – trial of unequal control group with pre and post – test. Population of the sample includes all students of first half of 2013-2014 educational year that have taken math courses in Saravan Unit and the number of them is 130. 65 subjects are in control group and 65 subjects are in test group. There were 35 female students and 30 male students in each group. Measurement tools in this study are researcher built math progress and Rion’s Intelligence test. Subjects of the study first participated in pre – tests and then instructed by cooperative learning method for 10 weeks and after that post – tests were done and required data were collected. In order to analyze the data, t-test was used. Results showed that math progress of test group with cooperative method, was higher than the control group that were instructed by direct method and the difference was significant .in addition, it was con-cluded that there is no significant math progress in two females and males groups.